Genetic analysis in horsegram (dolichos biflorus linn.) with special reference to photoperiodic response - Sreenivasan E (Department of Plant Breeding and Genetics, College of Horticulture, 2001)
A study was undertaken in the Department of Plant Breeding & Genetics of College of Horticulture, Vellanikkara, during 1993-2000 entitled "Genetic analysis in horsegram (Dolichos biflorus Lin.) with special reference to photoperiodic response" The main objectives were to identify stable, high-yielding, day-neutral • horsegram genotypes suitable for year-round cultivation and to understand the nature of gene action involved in the inheritance of photoperiodic response in the crop. The material consisted of 115 horsegram genotypes. Evaluation of the genotypes during rabi (traditional)indicated that enough variability exists among the genotypes with respect to seed yield and yield attributes. Studies on correlation and cause-effect relations among seed yield and yield attributes revealed that pod yield, . harvest index and haulms yield were the traits having maximum positive association and positive direct effect on seed yield. Duration to flowering or maturity did not have significant correlation with seed yield. Hence it is possible to have varieties that combine high yield and early maturity. Based on genetic diversity, the 115 genotypes were grouped into ten clusters, using Mahalanobis D2 statistics. It was found that genetic diversity existing among genotypes is not associated with their geographical origin. A selection index constructed based on seed yield, pod yield and harvest index was found to give 79.47 per cent gain in efficiency over selection based on yield alone. Genotypes selected on the basis of the preliminary evaluation were further tested over two seasons (rabi and summer) for three years (1997,1998 and 1999) in a comparative yield trial, to select best genotypes suitable for each seasons. The study revealed that the day-neutral genotype AK-42, is ideal for year-round cultivation. However, for cultivation during rabi, the photosensitive variety PHG-9 was found to